2009
DOI: 10.1111/j.1741-3737.2009.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Crisis and Marital Problems in Turkey: Testing the Family Stress Model

Abstract: Economic Crisis and Marital Problems in Turkey: Testing the Family Stress Model This paper applied the family stress model to the case of Turkey in the wake of the 2001 economic crisis. Using structural equation modeling and a nationally representative urban sample of 711 married women and 490 married men, we tested whether economic hardship and the associated family economic strain on families resulted in greater marital problems. Our results showed a modified family stress model applies to Turkey. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 15 publications
8
56
1
6
Order By: Relevance
“…Studies of families in Finland (Solantaus, et. al, 2004; Kinnunen & Pulkkinen, 1998), Korea (Kwon et al, 2003), Turkey (Aytac & Rankin, 2009), and the Czech Republic (Hraba, 2000) have shown that economic hardship is related to increased negative parenting behaviors. Given the severity and longevity of the recession in Europe, and prior work replicating the family stress model, it seems possible that with the appropriate data our findings might be replicated in other countries that have been affected by the Great Recession.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of families in Finland (Solantaus, et. al, 2004; Kinnunen & Pulkkinen, 1998), Korea (Kwon et al, 2003), Turkey (Aytac & Rankin, 2009), and the Czech Republic (Hraba, 2000) have shown that economic hardship is related to increased negative parenting behaviors. Given the severity and longevity of the recession in Europe, and prior work replicating the family stress model, it seems possible that with the appropriate data our findings might be replicated in other countries that have been affected by the Great Recession.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we assume that the existence of close family members and the strong normative demand to mutual support may even aggravate loneliness (studies showing the relationship between low socio-economic status, family conflicts and reduced well-being can be found in family research on the family stress model and in health research, e.g. Aytac and Rankin 2009;Barrett and Turner 2005;Choi and Marks 2011). In the remaining part of this paper, we would like to illustrate the strain on family solidarity from economic disadvantage more concretely (a) for societies with a very low societal wealth (as indicated by a low GDP), (b) for societies with a low to moderate societal wealth (as indicated by a low to moderate GDP) and (c) for societies with a moderate to high societal wealth (as indicated by a moderate to high GDP).…”
Section: An Integrative Modelmentioning
confidence: 99%
“…Het model suggereert dat er niet zozeer een direct negatief effect van de financiële druk op de huwelijksrelatie bestaat, maar eerder een indirect effect via psychologische stress. Verschillende studies hebben het family stress-model bevestigd, voornamelijk in de Verenigde Staten Parke e.a., 2004), maar ook in andere landen, zoals Finland (Kinnunen & Feldt, 2004), Turkije (Aytac & Rankin, 2009) en Korea (Kwon, Rueter, Lee, Koh & Ok, 2003). De studies die werden uitgevoerd buiten de Verenigde Staten leveren echter evidentie dat de effecten van financiële stress op de huwelijksrelatie zowel direct als indirect zijn.…”
Section: 1unclassified
“…Overeenkomstig de family stress-studies buiten de Verenigde Staten (bijvoorbeeld Aytac & Rankin, 2009;Kinnunen & Feldt, 2004; Kwon e.a., 2003) verwachten we dat de financiële stress van moeders en vaders zowel directe als indirecte effecten hebben op relatieconflicten. Gegeven het feit dat voorgaand onderzoek naar family stress-processen weinig evidentie opleveren met betrekking tot directe effecten van financiële stress naar het probleemgedrag van adolescenten (Conger e.a., 2010), verwachten we dat depressieve symptomen, relatieconflicten en opvoeding deze relatie mediëren.…”
Section: 3unclassified
See 1 more Smart Citation